The Ambiguous Arms of Aeneas - Fratantuono, Lee (Acta Classica Universitatis Scientiarum Debreceniensis, 2026)
Virgil subtly connects the scene of Dido’s discussion with her sister Anna about the new Trojan arrival Aeneas, and the later first arrival of the Trojans in Latium. By a careful corre-spondence between the two passages, Virgil portends the dark amatory rationale behind the sub-sequent outbreak of war in Italy